2000
DOI: 10.1074/jbc.m006456200
|View full text |Cite
|
Sign up to set email alerts
|

Lipoproteins Regulate Expression of the Steroidogenic Acute Regulatory Protein (StAR) in Mouse Adrenocortical Cells

Abstract: The production of hormones in steroidogenic tissues is dependent upon the availability of free cholesterol at the inner mitochondrial membrane, the site of the cholesterol side chain cleavage. In adrenocortical cells, adrenocorticotropin (ACTH) 1 stimulates hydrolysis of cholesteryl esters in lipid droplets, and transport of free cholesterol to mitochondria for use in steroid synthesis (1, 2). How free cholesterol in the outer mitochondrial membrane is transferred to the P450-cholesterol side chain cleavage (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…This experiment was performed twice with duplicate samples. conversion of cholesterol to hydroxycholesterol or steroid, affects LDL-induced increases in StAR mRNA levels (Reyland et al 2000). Taken together, these data suggest that increased substrate cholesterol availability may promote StAR protein synthesis.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…This experiment was performed twice with duplicate samples. conversion of cholesterol to hydroxycholesterol or steroid, affects LDL-induced increases in StAR mRNA levels (Reyland et al 2000). Taken together, these data suggest that increased substrate cholesterol availability may promote StAR protein synthesis.…”
Section: Discussionmentioning
confidence: 77%
“…In contrast to oxysterols, LDL increases StAR expression through upregulation of StAR promoter activity using an SF-1 site at 135 in the murine StAR promoter, suggesting involvement of SF-1 (Reyland et al 2000). The effect of LDL would probably not be enhanced by oxysterols since neither the P450 scc inhibitor aminoglutethimide, nor ketoconazole, which inhibits synthesis and Figure 7 Acute regulation of StAR protein by oxysterol is inhibited by cycloheximide (cyc).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…44). Oxysterols and lipoproteins have also been identified as chronic regulators of StAR gene and protein expression (45)(46)(47). Using an in vitro reporter assay, King et al (46) concluded that oxysterols regulate StAR in a process thought to be independent of new gene transcription.…”
Section: Discussionmentioning
confidence: 99%